2008
DOI: 10.1002/biof.5520330205
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke effect on total salivary antioxidant capacity, salivary glutathione peroxidase and gamma‐glutamyltransferase activity

Abstract: Saliva is the first biological fluid that inhaled cigarette smoke (CS) encounters. CS contains several carcinogens known to initiate and promote tumourigenesis and metastasis. One of the aims of this study was to establish if glutathione peroxidase and gamma-glutamyltranspherase (GGT) could be used as possible markers for evaluating the oral oxidative stress caused by smoking. The effect of CS on free radical generation was investigated using two methods. Using different assays, different antioxidants present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
3
19
0
2
Order By: Relevance
“…These findings were supported by various previous studies. 3,17,18 We found out that the cigarette smoke may alter the detoxification of hydrogen peroxide through a decrease of GSH-Px activity. 17 The overproduction of H 2 O 2 may leads to increase consumption of reduced glutathione and thus sufficient amount of reduced glutathione may not be available for the detoxification of H 2 O 2 leading to elevated oxidative stresses that is involved in a large number of diseases, including precancerous and neoplastic lesions of the oral cavity.…”
Section: Discussionmentioning
confidence: 92%
“…These findings were supported by various previous studies. 3,17,18 We found out that the cigarette smoke may alter the detoxification of hydrogen peroxide through a decrease of GSH-Px activity. 17 The overproduction of H 2 O 2 may leads to increase consumption of reduced glutathione and thus sufficient amount of reduced glutathione may not be available for the detoxification of H 2 O 2 leading to elevated oxidative stresses that is involved in a large number of diseases, including precancerous and neoplastic lesions of the oral cavity.…”
Section: Discussionmentioning
confidence: 92%
“…The activities of SOD, catalase and GPx were also increased in erythrocyte lysate. In addition, Greabu et al (2008) reported significantly decreased GPx activity in the saliva of smokers compared with that in non-smokers. Inconsistent results also have been found in various tissues.…”
Section: Anti-oxidant Statusmentioning
confidence: 98%
“…In one in vitro study we show that GPx levels in saliva are markedly decreased by prolonged incubation with CS. This suggests that GPx can be a potential marker for assessing OS caused by smoking [ 59 ]. These fi ndings have been re-confi rmed in a recent study on saliva from patients with chronic periodontitis.…”
Section: Saliva: Antioxidant Defense Systems and Oxidative Stress Biomentioning
confidence: 68%
“…We have analyzed the effect of CS on saliva in relation to GGT in an in vitro study. As expected the results show that exposure to CS resulted in a statistically signifi cant decrease of salivary GGT ( p < 0.01) [ 59 ]. We have also studied salivary GGT together with TAC and uric acid in a group of non-ferrous metals mine workers.…”
Section: Saliva: Antioxidant Defense Systems and Oxidative Stress Biomentioning
confidence: 86%
See 1 more Smart Citation